Employee Engagement, Organisational Commitment and Performance of Selected State Corporations in Kenya - Cheche, Stephen G.; Muathe, Stephen M.A.; Maina, Samuel M. (European Scientific Journal, ESJ, 2017)
The influence of employee engagement on organisational performance has been widely acknowledged and confirmed. However, there are scanty empirical investigations on the mediating role of organisational commitment on the relationship between employee engagement and organisational performance. Therefore, this study sought to investigate the mediating influence of organisational commitment on the relationship between employee engagement and performance of selected state corporations in Kenya. The study adopted a positivistic approach to investigate the relationships among and between the variables. Descriptive and explanatory research designs were used to describe the variables and establish the nature of the relationships among them. The study is based on employees of state corporations in research and training in the republic of Kenya. A sample of 378 respondents was selected using a multi stage sampling strategy. Data was analysed using descriptive and inferential statistics. The result indicates that employee engagement influences organisational performance and that the relationship is partially moderated by organisational commitment.